Performance of fecal S100A12 as a novel non-invasive diagnostic biomarker for pediatric inflammatory bowel disease: a systematic review and meta-analysis - Bendix Samarta Witarto; Visuddho Visuddho; Andro Pramana Witarto; Mahendra Tri Arif Sampurna; Abyan Irzaldy (Elsevier, 2023)
Objective: The incidence and prevalence of inflammatory bowel disease (IBD) in pediatric patients are increasing. Currently, the diagnostic method for IBD is inconvenient, expensive, and difficult. S100A12, a type of calcium-binding protein, detected in the feces of patients with IBD has recently been suggested as a promising diagnostic tool. Hence, the authors aimed to evaluate the accuracy of fecal S100A12 in diagnosing IBD in pediatric patients by performing a meta-analysis. Methods: The authors performed a systematic literature search in five electronic databases for eligible studies up to July 15, 2021. Pooled diagnostic accuracies of fecal S100A12 were analyzed as the primary outcomes. Secondary outcomes were standardized mean difference (SMD) of fecal S100A12 levels between IBD and non-IBD groups and a comparison of diagnostic accuracies between fecal S100A12 and fecal calprotectin. Results: Seven studies comprising 712 children and adolescents (474 non-IBD controls and 238 IBD cases) were included. Fecal S100A12 levels were higher in the IBD group than in the non-IBD group (SMD = 1.88; 95% confidence interval [CI] = 1.19-2.58; p < 0.0001). Fecal S100A12 could diagnose IBD in pediatric patients with a pooled sensitivity of 95% (95% CI = 88%-98%), specificity of 97% (95% CI = 95%-98%), and area under the receiver operating summary characteristics (AUSROC) curve of 0.99 (95% CI = 0.97-0.99). Fecal S100A12 specificity and AUSROC curve values were higher than those of fecal calprotectin (p < 0.05). Conclusion: Fecal S100A12 may serve as an accurate and non-invasive tool for diagnosing pediatric IBD.